A Three-dimensional kinematics analysis of a Koi Carp Pectoral Fin by digital image processing - Wang, Lei (2013)
Pectoral fins fascinate researchers for their important role in fish maneuvers. By possessing a complicated flexible structure with several fin rays made by a thin film, the fin exhibits a three-dimensional (3D) motion. The complex 3D fin kinematics makes it challenging to study the performance of pectoral fin. Nevertheless, a detailed study on the 3D motion pattern of pectoral fins is necessary to the design and control of a bio-inspired fin rays. Therefore, a highspeed photography system is introduced in this paper to study the 3D motion of a Koi Carp by analyzing the two views of its pectoral fin simultaneously. The key motions of the pectoral fins are first captured in both hovering and retreating. Next, the 3D configuration of the pectoral fins is reconstructed by digital image processing, in which the movement of fin rays during fish retreating and hovering is obtained. Furthermore, the method of Singular Value Decomposition (SVD) is adopted to extract the basic motion patterns of pectoral fins from extensive image sequences, i.e. expansion, bending, cupping, and undulation. It is believed that the movement of the fin rays and the basic patterns of the pectoral fins obtained in the present work can provide a good foundation for the development and control of bionic flexible pectoral fins for underwater propeller.